Sensory and physical qualities of peanut paste as affected by reduced dry blanching time - Sualog, Ma. Eden Concepcion; De Leon, Sonia Y. (1993.)
The study aimed to determine the effects of reduced dry blanching time on the sensory and physical qualities of peanut paste. The standard sensory and physical qualities of peanut paste were established by producing peanut pastes as described by Muego-Gbabasekharan and Resurreccion (1991). Two methods of dry blanching time-reduction were developed for a 500 - g sample size. These were the following : (1) use of wire rack, 40°C temperature and a dry blanching time of 3.25 hours; (2) use of wire rack, 49°C temperature and a dry blanching time of 1.50 hours. Results indicated that the standard pastes were dirty white in color, with slight peanut odor, very spreadable, smooth and with slight peanut flavor. The pastes had a water activity of 0.644. Peanut pastes which were dry-blanched on a wire rack at 40°C in 3.25 hours were light gray in color, with a characteristic peanut odor, moderately spreadable, smooth in texture, and with just recognizable peanut flavor. The pastes had a water activity of 0.710. T-test for significant difference at 5% level of significance showed that these pastes were not significantly different from the standard pastes in terms of all sensory attributes but these were significantly different in terms of water activity. Pastes which were dry-blanched on a wire rack at 49°C in 1.50 hours were light brown in color, with just recognizable peanut odor, slightly spreadable, coarse in texture and bland in flavor. These pastes had a water activity of 0.665. T-test for significant difference at 5% level showed that the pastes were significantly different from the standard pastes in terms of color. The odor, spreadability, texture, flavor and water activity of these pastes however, were not significantly different from that of the standard pastes.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Peanut products